Trees as huge flowers and flowers as oversized floral guides: the role of floral color change and retention of old flowers in Tibouchina pulchra - Brito, Vinícius L. G.; Weynans, Kevin; Sazima, Marlies; Lunau, Klaus (Frontiers in Plant Science, 2015)
Floral color changes and retention of old flowers are frequently combined phenomena restricted to the floral guide or single flowers in few-flowered inflorescences. They are thought to increase the attractiveness over long distances and to direct nearby pollinators towards the rewarding flowers. In Tibouchina pulchra, a massively flowering tree, the whole flower changes its color during anthesis. On the first day, the flowers are white and on the next three days, they change to pink. This creates a new large-scale color pattern in which the white pre-changed flowers contrast against the pink post-changed ones over the entire tree. We describe the spectral characteristics of floral colors of T. pulchra and test bumblebees´ response to this color pattern when viewed at different angles (simulating long and short distances). The results indicated the role of different color components in bumblebee attraction and the possible scenario in which this flower color pattern has evolved. We tested bumblebees´ preference for simulated trees with 75% pink and 25% white flowers resembling the color patterns of T. pulchra, and trees with green leaves and pink flowers (control) in long-distance approach. We also compared an artificial setting with three pink flowers and one white flower (T. pulchra model) against four pink flowers with white floral guides (control) in short-distance approach. Bumblebees spontaneously preferred the simulated T. pulchra patterns in both approaches despite similar rewards. Moreover, in short distances, pollinator visits to peripheral, non-rewarding flowers occurred only half as frequently in the simulated T. pulchra when compared to the control. Thefore, this exceptional floral color change and the retention of old flowers in T. pulchra favors the attraction of pollinators over long distances in a deception process while it honestly directs them towards the rewarding flowers at short distances possibly exploring their innate color preferences.